2021
DOI: 10.1055/s-0040-1722186
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α Blockade Corrects Monocyte/Macrophage Imbalance in Primary Immune Thrombocytopenia

Abstract: Primary immune thrombocytopenia (ITP) is an acquired autoimmune bleeding disorder. Monocytes and macrophages are the major cells involved in autoantibody-mediated platelet clearance in ITP. In the present study, we found increased percentages of peripheral blood proinflammatory CD16+ monocytes and elevated frequencies of splenic tumor necrosis factor-α (TNF-α)-expressing macrophages in ITP patients compared with healthy controls. Concurrently, we observed elevated TNF-α secretion in plasma as well as higher TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…TNF-α blockade decreased antibody-mediated platelet destruction and may be a promising therapeutic strategy for the management of ITP [32]. Anti-TNF-α therapy reduced the number of nonclassical monocytes and M1 macrophages, ameliorated the retention of platelets in spleen and liver, and increased the platelet count of ITP mice [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNF-α blockade decreased antibody-mediated platelet destruction and may be a promising therapeutic strategy for the management of ITP [32]. Anti-TNF-α therapy reduced the number of nonclassical monocytes and M1 macrophages, ameliorated the retention of platelets in spleen and liver, and increased the platelet count of ITP mice [32].…”
Section: Discussionmentioning
confidence: 99%
“…Other active components, like adenosine, a purinergic signaling molecule, showed good binding affinities with EGFR, TNF, STAT3, and ERBB2 than prototype ligands and were a well-known actor of the immune system and the inflammatory response both in physiologic and pathologic conditions 50]. It hypothesized that HQHG blocks TNF-α signaling pathway, resulting in remarkable attenuation of antibody-mediated platelet destruction [32]. This study investigated the intricate mechanism of HQHG treatment for ITP by utilizing an integrated network pharmacological and pharmacokinetics strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of T cell homeostasis is also thought to be one of the important reasons for the loss of immune tolerance in ITP. In clinical studies, it has been shown that CD16+ proinflammatory monocytes stimulate the Th1 response in the pathogenesis of ITP, and suppression of the proinflammatory monocyte response as a possible therapeutic target has been attempted to be targeted in vitro [47]. As a result, monocyte increase may be one of the main causes of immune dysregulation and may play different roles in the pathogenesis of ITP.…”
Section: Discussionmentioning
confidence: 99%
“…First, lipid absorption directly lowers the levels of inflammatory cytokines, such as tumor necrosis factor (TNF)-α [16], which are significantly elevated in patients with ITP [17]. Zhao et al reported that anti-TNF-α therapy reduced the number of non-classical monocytes and M1 macrophages and increased the platelet count in an ITP murine model [18]. Second, LDL-A suppresses the hyperactivation of macrophages [16,19], which are crucial for ITP pathogenesis by acting both as effector cells, phagocytizing platelets, and as antigen presenting cells, stimulating autoantibodies against platelet production [20].…”
Section: Discussionmentioning
confidence: 99%